A spontaneous gold(I)-azide alkyne cycloaddition reaction yields gold-peptide bioconjugates which overcome cisplatin resistance in a p53-mutant cancer cell line - Köster, Stephan David; Alborzinia, Hamed; Can, Suzan; Kitanovic, Igor; Wölfl, Stefan (Chemical science, 2012)
Solid-phase peptide synthesis (SPPS) is a versatile technique for the assembly of small to medium size peptides, that can help in the delivery of bound metal complexes to certain cellular compartments, for example in cancer cells. This work shows a new route to gold-peptide bioconjugates via a non-catalyzed [3 + 2] cycloaddition reaction of gold azides with alkynyl peptides. Gold(I) tetrapeptide conjugates with a mitochondria-targeting sequence were synthesized and display prolonged stability in the presence of thiol-containing biological media. Their antiproliferative potency against selected cancer cells (2-50 μM) corresponds to the lipophilicity of the conjugates. The cellular uptake of Au, determined by atomic absorption spectroscopy (AAS), shows that high initial uptake equals strong cytotoxicity. Respiration and acidification rates react immediately upon treatment with the Au-peptide conjugates, and a terminal breakdown of essential cellular functions is complete within ca. 12 h at most, as observed by online monitoring of the cancer cell metabolism in a microfluidic biosensor device (Bionas sensorchip system). The mode of action of these Au-peptide bioconjugates was elucidated by a variety of biochemical and cell biological experiments. First, a strong selective inhibition of the enzyme thioredoxin reductase (TrxR), a regulator of cellular redox processes, was found. In this context, elevated levels of reactive oxygen species (ROS) and strong effects on the respiration of isolated mouse liver mitochondria were found. These finally lead to cell death via apoptotic pathways, as indicated by flow cytometry, low mitochondrial membrane potential (MMP) and DNA fragmentation. Intriguingly, cisplatin-resistance in p53-mutant MDA-MB231 breast cancer cells could be overcome by the Au-peptide conjugates presented herein.